Psychosocial Stress, Job Satisfaction, Motivation and well-being of Professionals in Special Education Centers - Aziz, Abdul; Saif Ur Rehman; Faiza Saeed Ch.; Nayab Islam; Malaika Younas (Dialogue Social Science Review (DSSR), 2025)
In low- income countries professionals in special education centers face unique psychosocial stressors and challenges often overlooked in global research. The current study analyzed the psychosocial stress, job satisfaction and motivation among 150 special educators in Lahore division using a cross sectional survey. A validated questionnaire (Cronbach’s a = .898) evaluate the important role of intrinsic /extrinsic motivation, job satisfaction, and psychosocial stress in special education teachers. The outcomes of this study showed intrinsic factors like student rehabilitation (M = 4.66), parent cooperation (M = 4.63), and student relationships (M = 4.65) were most influential, aligning with Herzberg theory. Extrinsic motivators like recognition (M = 4.06) and promotion (M = 2.58), had less impact, highlights systemic inequalities. While educators were satisfied with colleagues (M = 3.92) and work environment (M = 3.94), 53% reported promotion dissatisfaction as their primary stressor. In regards of gender, females (44%) experienced job related stress more than males (32%), despite similar motivation and satisfaction levels (p> 0.05). An unexpected phenomenon emerged during research that the specific cultural concern revealed the fusion of professional and societal burdens that 39% feared was transmitted disabilities to their own child. The regression analysis evidence the interpersonal relationship (β = .23, p = 0.005) and workplace condition (β = .22, p = .007) as significant drivers of satisfaction. A progression of career modified and gender focused on mental health supports to reduce the burnout in demanding educational roles founded by the advocate for context-specific solutions. The current study enhances the mental support to the professionals by connecting the global theories of local experience.